Numerical Investigation of the Nonlinear Coupled Fractional Massive Thirring Equation Using Two-Scale Approach. (13th June 2022) - Liu, Jinxing; Nadeem, Muhammad; Habib, Mustafa; Karim, Shazia; Or Roshid, Harun
Abstract : In this paper, we investigate the numerical solution of the coupled fractional massive Thirring equation with the aid of He's fractional complex transform (FCT). This study plays a significant aspect in the field of quantum physics, weakly nonlinear thrilling waves, and nonlinear optics. The main advantage of FCT is that it converts the fractional differential equation into its traditional parts and is also capable to handle the fractional order, whereas the homotopy perturbation method (HPM) is employed to tackle the nonlinear terms in the coupled fractional massive Thirring equation. An example is illustrated to present the efficiency and validity of the two-scale theory. The solutions are obtained in the form of series with simple and easy computations which confirm that the present approach is good in agreement and is easy to implement for such type of complex systems in science and engineering.